Analisis Ideologi Ibuisme pada Konten Iklan Susu Anak - Patria Yulida Augustine; Gita Juniarti (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2022)
Advertising aims to convey a persuasive message so that the audience buys the products offered. Besides, it also contains implied ideology. The ideology is conveyed implicitly with visuals and words in the advertisement. This study aimed to examine the ideology implied in the five advertisements for children's milk broadcast on television. This research used the content analysis research method. The population was children's milk advertisements broadcast on television. The samples were the five advertisements for children's milk that were consumed the most in 2020, i.e. Enfagrow, Pediasure, Chil Kid Morinaga, Nestle Lactogrow, and SGM. The units studied were physical, syntactic, and thematic units. The study results showed that the advertisements for children's milk contain an implied ideology. The ideology was motherism ideology, where a mother is fully responsible for family integrity and domestic work. This was shown from the most dominant vocabulary that appeared in the advertisement, explanation of the milk, the role that is dominated by the mother, and scenes that occur in the advertisement. Some advertisements showed father figures and citizens as extras. However, the mother role who made milk in kitchen, and was responsible for the ideas initiated by her child, showed the motherism ideology implicitly